Environmental Characteristics of Modern Systems of Domestic Use of Fuel. Part 2. Pollutants Formation by Natural Gas Combustion in Atmospheric Burners: Experimental Studies - B. S. Soroka; V. V. Horupa (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The Gas Institute of the National Academy of Sciences of Ukraine performs comprehensive studies of the formation of toxic emissions in the flame of atmospheric burners and beyond the visible burning cones (“rich” primary flame). The experiments are based on the proven significant content of harmful substances in the combustion products of gas fuel in household appliances and on direct contact of consumers with gas emissions during the operation of the stoves. A methodology for the experimental researches of the harmful emissions formation has been proposed while the computerized firing rig serving as the diagnostic facility has been developed for studying the combustion of hydrocarbon gases in the burners of household stoves. Carbon oxides CO and nitrogen oxides NO and NO2 are considered as toxic emissions, while the primary air excess coefficient and the heat load of the burner are considered as variable parameters. Under operating conditions of a gas stove, its variable characteristics are the gas pressure in front of the nozzle of the atmospheric burner and its thermal power. When optimizing the design of burners, the determinant value of the stability of burning, energy and environmental indicators of fuel combustion is the coefficient of excess of primary air λpr at a given gas pressure before the burner. The influence of this coefficient on the formation of CO, NO, NO2 is established, and the possibility of emissions with a high concentration of nitrogen dioxide is proved. Since the concentration of [NO] decreases with an increase in λpr, and the absolute level of [NO2] concentrations is not significantly affected by the value of λpr, it is determined that the proportion of [NO2] concentration in the [NOx] = [NO] + [NO2] compound increases with an increase in the primary air excess coefficient.